Scleral Buckling for Primary Retinal Detachment: Outcomes of Scleral Tunnels versus Scleral Sutures - Matthew R. Starr; Edwin H. Ryan; Anthony Obeid; Claire Ryan; Xinxiao Gao; Malika L. Madhava; Sean M. Maloney; Adam Z. Adika; Krishi V. Peddada; Kareem Sioufi; Luv G. Patel; Michael J. Ammar; et al. (Journal of Ophthalmic & Vision Research)
Abstract Purpose: There are primarily two techniques for affixing the scleral buckle (SB) to the sclera in the repair of rhegmatogenous retinal detachment (RRD): scleral tunnels or scleral sutures. Methods: This retrospective study examined all patients with primary RRD who were treated with primary SB or SB combined with vitrectomy from January 1, 2015 through December 31, 2015 across six sites. Two cohorts were examined: SB affixed using scleral sutures versus scleral tunnels. Pre- and postoperative variables were evaluated including visual acuity, anatomic success, and postoperative strabismus. Results: The mean preoperative logMAR VA for the belt loop cohort was 1.05 ± 1.06 (Snellen 20/224) and for the scleral suture cohort was 1.03 ± 1.04 (Snellen 20/214, p = 0.846). The respective mean postoperative logMAR VAs were 0.45 ± 0.55 (Snellen 20/56) and 0.46 ± 0.59 (Snellen 20/58, p = 0.574). The single surgery success rate for the tunnel cohort was 87.3% versus 88.6% for the suture cohort (p = 0.601). Three patients (1.0%) in the scleral tunnel cohort developed postoperative strabismus, but only one patient (0.1%) in the suture cohort (p = 0.04, multivariate p = 0.76). All cases of strabismus occurred in eyes that underwent SB combined with PPV (p = 0.02). There were no differences in vision, anatomic success, or strabismus between scleral tunnels versus scleral sutures in eyes that underwent primary SB. Conclusion: Scleral tunnels and scleral sutures had similar postoperative outcomes. Combined PPV/SB in eyes with scleral tunnels might be a risk for strabismus post retinal detachment surgery.